Stages of the creative path of V. V. Pidvysotskii (on the 160th anniversary of his birth) - Gamaliia, V. M.; Ruda, S. P. (History of science and technology, 2018)
The article is dedicated to the memory of the outstanding Ukrainian pathologist, endocrinologist, immunologist V. V. Pidvysotskii. Stages of his creative path, the results of scientific and scientific-organizational activity are outlined. Information on the scientific school founded by him has been given. His portrait as a friendly, benevolent, all-round gifted person has been recreated.